INFLUENCE OF PROCESSING METHODS OF CULTIVATION ON FORMATION OF INDICATORS OF QUALITY OF GRAIN OF WHEAT WINTER IN THE CONDITIONS OF THE NORTHERN STEPPE - Козечко, В. І. (Scientific Progress & Innovations, 2014)
Results of the conducted pilot researches testify that at cultivation of various sorts of wheat winter after a spring rape in the conditions of the northern Steppe of Ukraine, receiving the most qualitative grain, the third class of quality, provides sowing on 25 September and on 5 October. Sowing on 5 and 15 September provided grain, generally the fifth and fourth classes of quality. Among sorts of wheat winter which were studied in the experiences, the greatest protein content (11,2–13,0%) and glutens (17,5–22,7%) in grain Selyank's sort differed. The smallest Podolyank's sort of – 10,6–12,5 and 17,1–21,9% had these indicators respectively. The volume of the bread received from a flour of wheat of winter of a sort of Selyanka, was the highest. So, on the average for 2008–2010 it fluctuated from 495 cm3 when sowing on 5 September seeding rate of 4 million units germinating seeds/ha to 612 cm3 when sowing on 5 October the same norm. Influence of seeding rate on indicators of quality of grain is established. So, high protein content and glutens in grain, and also the volume of bread are noted on experience options where sowing carried out norm of 4 million units germinating seeds/ha. The increase in seeding rate led to reduction of these indicators. Average, over years of research, the highest yield sort Selyanka formed (4,89 t per ha) when sowing on 25 September norm of 5 million units germinating seeds/ha. The maximum productivity of a plant of a grade of Zolotokolosa – 4,20 and 4,19 t per ha formed, respectively, when sowing on 5 October norm of 6 million units germinating seeds/ha and on 25 September seeding rate of 5 million units germinating seeds/ha. The low among grades productivity was formed by a sort of Podolyanka at which it fluctuated, during carrying out researches, within 2,99–3,75 t per ha.